The influence of political and professional activities of k. Trilliovskyi on the formation of Ukrainian political and legal thought - Fedyk L.; Lytsur M. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
The purpose of the study is to reveal the impact of K. Trilliovskyi’s practical activities on the formation of Ukrainian political and legal thought. Methods. The author uses the historical and genetic method to identify the origins of certain legal ideas in Ukrainian socio-political and legal thought. The praxeological method was used to study the peculiarities of K. Trilliovskyi’s activities as a lawyer and politician, and to determine their effectiveness. The comparative method was used for a deeper study of K. Trilliovskyi’s legal ideas by comparing them with the ideas of M. Drahomanov. Results. The study identifies three areas of activity of K. Trilliovskyi which influenced the formation of legal thought in Galicia in the second half of the nineteenth century: as a politician, national figure and lawyer. The author analyses the role of Kyrylo Tryliovskyi in organising the work of the political organisation “Narodna Volia”. It is emphasised that the politician was an active organiser of meetings and events. He was a speaker who brought up for discussion the most important issues for the ordinary population. K. Trilliovskyi’s ideas on the implementation of the idea of the Ukrainian national state and the implementation of Austro-Hungarian legislation in the field of protection of the rights of the Ukrainian population are revealed. Scientific novelty. It is proved that the legal ideas of K. Trilliovskyi were based on the ideas of liberalism. The key for the lawyer was the substantiation of civil, economic, political, social and cultural rights and freedoms. It is shown that K. Trilliovskyi, as a member of the Russian-Ukrainian Radical Party, substantiated the idea of unity and the creation of a nation-state, and as a deputy, he implemented these ideas at the legislative level. Practical significance. The scientific findings presented in the article can be used in legal education work among the population with a view to raising the level of their legal awareness and legal culture, and forming a democratic legal outlook.